The redbreast - Nesbø, Jo, 1960- (Nesbø, Jo, 1960- Harry Hole series, 2017)
"Detective Harry Hole embarrassed the force, and for his sins he's been reassigned to mundane surveillance tasks. But while monitoring neo-Nazi activities in Oslo, Hole is inadvertently drawn into a mystery with deep roots in Norway's dark past—when members of the nation's government willingly collaborated with Nazi Germany. More than sixty years later, this black mark won't wash away, and disgraced old soldiers who once survived a brutal Russian winter are being murdered, one by one."--